NUTRITIONAL VALUE AND GLYCEMIC LOWERING EFFECT OF SPROUTED FENUGREEK (Trigonellafoenumgracecum L) SEEDS - Laminu HH; Farida M; Patient AT (Ntec Specialist, 2017)
Background: Fenugreek, Trigonellafoenumgraecum L, is an annual herb grown in various countries around the world. The seeds are considered important both as food item and medicinal plant. Sprouting is a simple processing method, which involves soaking or steeping dry seeds, cereals or legumes in water until they are saturated followed by germination. Objective: The present study investigate the nutritional value and glycemic effect of sprouted fenugreek. Methodology: Fenugreek seeds were sprouted for 48 hours. The sprouted and raw fenugreek seeds were analysed for chemical composition, in vitro carbohydrate and protein digestibility and antinutritional factors using standard laboratory methods. Thirty male Wister rats were used to evaluate the effect of sprouted and raw fenugreek on weight and their glycemic response. Results: The sprouted fenugreek had a higher Protein content (29.33±0.60 %) than the raw fenugreek (26.33±0.65%).The result of the mineral element composition showed significant (P less than 0.05) increase in the levels of calcium, iron, magnesium and zinc in the sprouted fenugreek. Reductions of 71.41% phytic acid and 63.30% tannins were observed in the sprouted fenugreek which led to significant (P less than 0.05) increase in in vitro carbohydrate and protein digestibility of the sprouted fenugreek. Decrease in weight of rats was observed both in the group of rats that were fed raw fenugreek and sprouted fenugreek. The weight loss in the group of rats that were fed sprouted fenugreek was significantly (P less than 0.05) more than that of the group that were fed raw fenugreek. The raw and the sprouted fenugreek exhibited glycemic lowering effect but sprouted fenugreek had slightly higher glycemic lowering effect. Conclusions: The finding concluded that sprouted fenugreek had improved nutritional value and higher glycemic lowering effect.